2020
DOI: 10.1007/s12070-020-02279-w
|View full text |Cite
|
Sign up to set email alerts
|

Does Pectoralis Major Myocutaneous Flap Cause the Shoulder Morbidity: A Clinical Comparative Study

Abstract: The aim was to compare the morbidity of shoulder function following modified radical neck dissection with and without Pectoralis Major Myocutaneous muscle flap (PMMC) harvest in head and neck cancer patient to determine the effect of PMMC flap harvest on shoulder function and also to determine the effect of physiotherapy. Materials and methods: Prospective study involving two groups study group of 20 patients with MRND, with PMMC flap reconstruction as part of head and neck cancer surgery and control group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…From the standpoint of donor-site morbidity, FTT has a minimal impact in long-term function, 24 which contrasts to the shoulder and arm morbidity associated with pectoralis muscle flaps. 25,26 However, FTT requires a higher acuity of care as well as additional equipment and expertise that may result in higher costs. 27 Interestingly, a recent study found this technique to be cost-effective compared with locoregional flaps, even in patients with localized head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the standpoint of donor-site morbidity, FTT has a minimal impact in long-term function, 24 which contrasts to the shoulder and arm morbidity associated with pectoralis muscle flaps. 25,26 However, FTT requires a higher acuity of care as well as additional equipment and expertise that may result in higher costs. 27 Interestingly, a recent study found this technique to be cost-effective compared with locoregional flaps, even in patients with localized head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…From the standpoint of donor-site morbidity, FTT has a minimal impact in long-term function, which contrasts to the shoulder and arm morbidity associated with pectoralis muscle flaps . However, FTT requires a higher acuity of care as well as additional equipment and expertise that may result in higher costs .…”
Section: Discussionmentioning
confidence: 99%